Subinhibitory concentrations of glabridin from Glycyrrhiza glabra L. reduce Listeria monocytogenes motility and hemolytic activity but do not exhibit antimicrobial activity - Liao, Chengshui; Yu, Chuan; Guo, Jinxiang; Guan, Mengxiang (Frontiers in Microbiology, 2024)
Increases in the virulence and survival of some pathogens in the presence of subinhibitory concentrations of antibiotic have been reported. However, research on the effects of subinhibitory concentrations of antimicrobial substances derived from traditional Chinese medicine on pathogens is still insufficient. Glabridin is a well-known active isoflavone found in licorice root that possesses a wide range of biological activities. Therefore, in this study, Listeria monocytogenes (L. monocytogenes) exposed to subinhibitory concentrations of glabridin was used as the research object. The minimum inhibitory concentration (MIC) was determined for L. monocytogenes. We investigated the impacts of subinhibitory concentrations of glabridin on the morphology, motility, biofilm formation, adherence, and survival of L. monocytogenes. The results indicated that the MIC of glabridin for L. monocytogenes was 31.25 μg/mL. At 1/8, 1/4, or 1/2 of the MIC, glabridin did not affect the growth, morphology, flagellar production, or biofilm formation of L. monocytogenes. However, subinhibitory concentrations of glabridin inhibited bacterial swimming and swarming motility and decreased the hemolytic activity of L. monocytogenes. Glabridin reduced the hemolytic activity of L. monocytogenes culture supernatants. The results also showed that subinhibitory concentrations of glabridin had no toxic effect on RAW264.7 cells but decreased the intracellular growth of L. monocytogenes in RAW264.7 cells. Furthermore, subinhibitory concentrations of glabridin triggered ROS production but did not induce MET formation in macrophages. In addition, glabridin did not enhance the capacity of L. monocytogenes to trigger METs or the extracellular killing of macrophages by METs. Thus, we conclude that subinhibitory concentrations of glabridin reduce L. monocytogenes motility and hemolytic activity but do not exhibit antimicrobial activity. Glabridin could be an interesting food additive as a bacteriostatic agent with anti-Listeria activity.